The Effect of Diabetes Self-Management Education (DSME) on Improving Self-Management and Quality of Life in Millitus Type 2 Diabetes - Reza Diko Utama; Indasah Indasah; Siti Farida Noor Layla (Journal for Quality in Public Health, 2021)
Self-management is a form of self-regulation. The purpose of this study was to determine the effect of Diabetes Self-Management Education (DSME) on the Improvement of Self-Management and Quality of Life in Type II Diabetes Millitus Patients. This research method is True-Experiment Pre-Test and Post-Test design. DSMQ and WHOQOL instruments. Independent Variable (DSME) Dependent variable Self-management and quality of life. The subjects of the control group were 55 people and the intervention group was 55 people. Wilcoxon data analysis, Maan-Whitney and Path Analysis. The results of the comparison of self-management between the intervention group and the control group, a significance value of 0.000 less than 0.05 (p <0.05), indicating that the group given effective intervention significantly improved self-management compared to the group that was not given the intervention. The results of the comparison of the quality of life of the intervention group and the control group, the significance value of 0.000 less than 0.05 (p <0.05) indicates that the group given the intervention was more effective in improving the quality of life significantly than the group that was not given the intervention. There is an effect of Diabetes Self-Management Education (DSME) on the Improvement of Self-Management and Quality of Life for Type II Diabetes Millitus Patients in the Work Area of the Kempo Health Center, Kempo District. DSME is a process to facilitate knowledge, skills and abilities in self-care (Self-Management) and quality of life